Effects of NPK Briquette on Rice (Oryza sativa) in Tidal Flooded Ecosystem - Islam, M Sh; Rahman, F; Hossain, ATMS (The Agriculturists, 2012)
An experiment was conducted at the Bangladesh Rice Research Institute, R/S Sagordi farm, Barisal to evaluate the effectiveness of NPK briquette on rice in tidal flooded soil condition during Boro season, 2010. NPK briquettes of size 2.4 g and 3.4 g were compared with urea super granules (USG) and prilled urea (PU), each supplemented with PKS. The results showed that NPK briquettes, USG and PU produced statistically similar grain yield. N-treated plots (briquettes, USG and PU) gave significantly higher grain yield than N control. The highest grain yield (7.47 t ha-1) was observed in NPK briquette (2.4 g × 2) followed by PU. There was no significant difference between N control and absolute control plots in respect of yield indicating that N was the only yield limiting factor under that condition. The NPK briquettes showed higher agronomic efficiency than PU and USG. The small size briquettes (2.4 g) could save 33 kg N ha-1 compared to recommended PU. There was no residual effect of NPK briquettes on soil chemical properties. The NPK briquettes were found beneficial to the farmers in tidal ecosystem. Keywords: NPK briquette; USG; prilled urea; agronomic efficiency; nutrient uptake DOI: http://dx.doi.org/10.3329/agric.v9i1-2.9477 The Agriculturists 2011; 9(1&2): 37-43